Implementation of Word Chain Game in Vocabulary Learning at MA Miftahul Ulum Bettet Pamekasan - Kirom, Amilinal; Yuliawati, Fitrah; Setiawan, Arisandi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to determine the application of word chain games in learning English vocabulary and its impact on the involvement of students in class XI-S7 at MA Miftahul Ulum Bettet Pamekasan. The research method used is descriptive qualitative approach with data collection techniques through observation, interview, and documentation. The results showed that the word chain game was able to increase students' active participation during the learning process, help strengthen the memory of the vocabulary that had been learned, and create a fun and interactive learning atmosphere. In addition, this method also makes students more enthusiastic and confident in using new vocabulary. Thus, word chain game can be considered as an effective alternative strategy in English vocabulary learning at MA level. The use of this method is highly recommended to improve the quality of teaching-learning process which does not only focus on memorization, but also involves students actively.